The role of in-bore magnetic resonance imaging guided biopsy for the detection of clinically significant prostate cancer - Shoji, Sunao (Translational Cancer Research, 2017)
Clinically significant prostate cancers have been rendered detectable with the advent of multi-parametric magnetic resonance imaging (mpMRI) (1). Diagnosis and spatial localization of these lesions is important in their management and/or active surveillance (2). In-bore MRI-guided biopsy (MRGB) can be performed with mpMRI localization (3), although the procedure can be difficult and time-consuming, and is not considered routine for several reasons. First, the biopsy takes at least 30 minutes, a long time for patients to lie prone. Second, MRI-safe biopsy devices are very expensive.